Heightened Negative Affects Associated With Neurotic Personality in Behavioral Addiction - Asaoka, Yui; Won, Moojun; Morita, Tomonari; Ishikawa, Emi; Goto, Yukiori (Frontiers in Psychiatry, 2020)
Although studies have demonstrated that negative affects are critical attributes of drug addiction, this has remained less clear in behavioral addiction. In this preliminary study with a relatively small number of samples, we investigated negative affects in patients diagnosed with behavioral addiction, particularly paraphilia and kleptomania. Negative affects were examined using self-rating questionnaire, and further evaluated by objective assessments in behavioral addicts and normal subjects. Explicit, self-referential negative affects, such as anxiety, stress, and depression, were higher in behavioral addicts than control subjects. Such self-referential negative affects were, although not entirely, consistent with objective evaluations by others and blood stress hormone concentrations. Further investigation of personality traits in behavioral addicts unveiled that heightened negative affects were associated with stronger neurotic personality in behavioral addicts than normal subjects. These results suggest that behavioral addiction, such as paraphilia and kleptomania, may be characterized by heightened negative affects attributable to stronger neurotic personality.